Growing in the shadow of antifascism : remembering the Holocaust in communist Eastern Europe - Stach, Stephan HerausgeberIn; Hallama, Peter 1982- HerausgeberIn; Bohus, Kata HerausgeberIn (Central European University Press, 2022)
"Reined into the service of the Cold War confrontation, antifascist ideology overshadowed the narrative about the Holocaust in the communist states of Eastern Europe. This led to the Western notion that in the Soviet Bloc there was a systematic suppression of the memory of the mass murder of European Jews in the. Going beyond disputing the mistaken opposition between "communist falsification" of history and the "repressed authentic" interpretation of the Jewish catastrophe, this work presents and analyzes the ways as the Holocaust was conceptualized in the Soviet-ruled parts of Europe. The authors provide various interpretations of the relationship between antifascism and Holocaust memory in the communist countries, arguing that the predominance of an antifascist agenda and the acknowledgement of the Jewish catastrophe were far from mutually exclusive. The interactions included acts of negotiation, cross-referencing, and borrowing. Detailed case studies describe how both individuals and institutions were able to use anti-fascism as a framework to test and widen the boundaries for discussion of the Nazi genocide. The studies build on the new historiography of communism, focusing on everyday life and individual agency, revealing the formation of great variety of concrete, local memory practices"--